Association between anxiety and skin conductance according to the intensity of shaking of virtual reality images - Kim, Dong Jun; Kim, Hyewon; Kim, Kiwon; Kim, Min-Ji; Jeon, Hong Jin (Frontiers in Psychiatry, 2023)
Introduction: Despite advantages of Virtual Reality (VR), cyber-sickness make it difficult to apply VR to those who are already anxious and in distress. Skin conductance (SC) is widely used as a bio-signal reflecting anxiety. It is positively correlated with anxiety. The objective of this study was to determine the association between SC and anxiety in VR. Methods: Healthy volunteers with moderate-to-high stress defined as a Perceived Stress Scale-10 (PSS-10) score ≥ 20 were enrolled. STAI-X-1 was used to measure anxiety and Galvanic Skin Response was used to measure SC. This study used an open, randomized, crossover design. In this study, 360-degree videos consisted of two types, less dizzying video (G1) and more dizzying video (G2). We randomized subjects into two groups according to video exposure order: G1 after watching G2 (Order 1) and G2 after watching G1 (Order 2). Of 81 subjects, the average age (± SD) was 39.98 ± 10.94 years for the Order 1 group and 36.54 ± 12.44 years for the Order 2 group. Results: Anxiety was significantly decreased in the Order 2 group (p < 0.035) after watching videos, whereas there was no significant change in anxiety in the Order 1 group. In both groups, SC was significantly increased after exposure to a dizzying video. Mean difference (SD) between the second VR video and baseline SC was 1.61 (1.07) (p < 0.0001) in the Order 1 group and 0.92 (0.90) (p < 0.0001) in the Order 2 group, showing a significant difference between the two groups (p < 0.003). However, there was no significant difference between the two groups (p < 0.077) after baseline correction. Conclusion: Anxiety was decreased significantly in the Order 2 group. The Order 1 group showed a high rate of change in skin conductivity. It is possible to reduce SC and anxiety by viewing a less dizzying VR video first and then viewing a more dizzying video later.